THE EFFECT OF FINANCIAL DISTRESS AND ACCOUNTING CONSERVATISM ON TAX AVOIDANCE WITH LEVERAGE AS MODERATING VARIABLE - Hidayanto N.; Erasashanti A.P.; Winarti C.E.; Wahyuningsih E. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
Tax avoidance is the activity of managing the company's finances to avoid the larger amount of tax burden legally without violating the prevailing laws. This study aims to analyze the effect of financial distress and accounting conservatism on tax avoidance with leverage as moderating variable. The data used in this study was obtained from the annual financial statements of manufacturing companies listed on the Indonesian Stock Exchange during the period of 2015 to 2019 based on the Jakarta Stock Industrial Classification (JASICA) system. This study used 340 samples which obtained through purposive sampling method. The analytical method used in this study is panel data regression analysis. The results of the study which used fixed effect model showed that financial distress and accounting conservatism have a significant negative effect on tax avoidance, while leverage has no effect on tax avoidance, and leverage moderates the influence of financial distress and accounting conservatism on tax avoidance.